ARCHAEOLOGICAL SURVEY AT PELABUHAN RATU SITE AND CILETUH SITE, SUKABUMI, WEST JAVA: REVEALING THE POSSIBILITY OF MARITIME CULTURAL LANDSCAPE AND THE GOLDEN PATH ON PREHISTORIC PERIOD - Akbar, Ali (International Review of Humanities Studies, 2023)
Research on Prehistoric Era, especially megalithic culture, has been conducted many times in Indonesia. Generally, the results of the study show that megalithic culture produces structures and buildings of large stones. These remains are often found in mountains or hills. However, the results of the research that the author did in Sukabumi, West Java show different outcome. The author conducted a survey at Pelabuhan Ratu Site and Ciletuh Site. These two sites can be said as newly discovered sites. The method used was an archaeological survey by visiting the site and carefully observing the structure and megalithic buildings on both sites. The results of the study found statues and stepped pyramid in the coastal area. The two sites are located near the sea, so it is more appropriate if we consider that the community developed maritime cultural landscape. Then, the two sites are close to the source of gold. The factor of proximity to valuable mineral resources seems to be a consideration of this site selection. Easy access to interact with the community from other sites, even from other islands, may also be a consideration of location selection.